Chloroplast DNA variation in Epipactis atrorubens populations from northern Greece. Issue 1 (2nd January 2017) - Drouzas, Andreas D.; Charitonidou, Martha; Tsiftsis, Spyros
Abstract: Epipactis Zinn. is a highly diverse genus, with numerous taxa naturally occurring throughout Europe. While their morphological variability has resulted in contradictory opinions about their taxonomy, the knowledge of the genetic variation of many of its species is limited. Such an example is E. atrorubens in the Balkan Peninsula. In this work, the cpDNA variation of seven E. atrorubens populations from northern Greece and of one population from Germany has been investigated by means of PCR-RFLP markers. Two regions of the cpDNA were studied ( trn H- psb A, trn L intron) and four PCR-RFLP markers were employed ( trn H- psb A/ Hae III, trn H- psb A/ Hinf I, trn H- psb A/ Vsp I, trn L/ Mbo I), which have revealed variation in other Epipactis species. The results demonstrate limited genetic variability in the studied populations, as only one haplotype was present in all the populations (both Greek and German), with the exception of Mt. Menikion (Greece) where a second haplotype was also recorded. This limited variation may be attributed to the properties of the genetic markers involved, to the conserved status of the two cpDNA regions in this species or to factors related to the biology and evolutionary history of E. atrorubens . The presence of a second haplotype only in Mt. Menikion could be attributed to a hybridisation event in the past and/or to the potential existence of a glacial refugium on this mountain.